Hip Labral Tears among Asymptomatic Professional Hockey Players Identified on MRI: Four-year Follow-up Study - Gallo, Robert A. (Orthop J Sports Med, 2013)
OBJECTIVES: We have previously reported on the prevalence of pathologic hip findings on the MRIs of asymptomatic professional hockey players. The significance of these findings, found in the asymptomatic player, is unknown. The purpose of this study is to report clinical follow-up of this cohort at four years. METHODS: 21 professional hockey players with no previous hip/groin pain underwent hip/pelvis MRI. Self-reported symptoms were measured using a modified Oswestry Disability Questionnaires at one and two years following MRI. Games played for each player were followed over a four-year period. Variance of games played greater than five per year compared to baseline (games played year prior to MRI) were explored for specific injury. RESULTS: 16/21 and 14/21 minor league hockey players were available at one- and two-year follow-up, respectively. 19/21 players remained active within four years. Fourteen remained at same level, four advanced to higher level of play, and one was demoted to a lower level at the end of four years. At one-year follow-up, two players (both with labral tear) admitted to groin pain; one, who also had bilateral adductor tendinosis, eventually missed games due to lateral hip pain in the third season after the MRI. At two-year follow-up, one other player (bilateral labral tears) admitted to hip tightness for a week but did not miss any games. Of the15 players that had an asymptomatic labral tear, two players advanced to NHL, ten remained at same level, one demoted, and two retired within four-year follow-up period. Among 9 players with labral tears on original MRI and available for questioning at two years, seven had no hip or groin symptoms and only one of 3 “symptomatic” players missed any games or sought treatment. Only four players had no abnormalities on MRI. None developed symptoms within two years. 3/4 remained at same level while the other advanced to the NHL. CONCLUSION: Although common on MRI among asymptomatic professional hockey players, hip labral tears produce symptoms in 20% within two years, but only 6.7% result in missed games within four years due to hip-related pain.